Novel insurance-linked credit product that covers loan repayment during drought for Kenyan smallholder farmers - CGIAR Research Program on Policies, Institutions, and Markets (2020)
The tool was successfully piloted in several districts of Kenya in 2018-2019. In 2020 the results were published in a journal article and the innovation was presented in an IFPRI podcast.